Growth in stratospheric chlorine from short‐lived chemicals not controlled by the Montreal Protocol. Issue 11 (1st June 2015) - Hossaini, R.; Chipperfield, M. P.; Saiz‐Lopez, A.; Harrison, J. J.; von Glasow, R.; Sommariva, R.; Atlas, E.; Navarro, M.; Montzka, S. A.; Feng, W.; Dhomse, S.; Harth, C.; et al.
Abstract We have developed a chemical mechanism describing the tropospheric degradation of chlorine containing very short‐lived substances (VSLS). The scheme was included in a global atmospheric model and used to quantify the stratospheric injection of chlorine from anthropogenic VSLS ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1d0rwsvm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ClyVSLS</alternatives>) between 2005 and 2013. By constraining the model with surface measurements of chloroform (CHCl3), dichloromethane (CH2Cl2), tetrachloroethene (C2Cl4), trichloroethene (C2HCl3), and 1, 2‐dichloroethane (CH2ClCH2Cl), we infer a 2013 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1d0rwssh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ClyVSLS</alternatives> mixing ratio of 123 parts per trillion (ppt). Stratospheric injection of source gases dominates this supply, accounting for ∼83% of the total. The remainder comes from VSLS‐derived organic products, phosgene (COCl2, 7%) and formyl chloride (CHClO, 2%), and also hydrogen chloride (HCl, 8%). Stratospheric <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1d0rwtm8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ClyVSLS</alternatives> increased by ∼52% between 2005 and 2013, with a mean growth rate of 3.7 ppt Cl/yr. This increase is due to recent and ongoing growth in anthropogenic CH2Cl2—the most abundant chlorinated VSLS not controlled by the Montreal Protocol.